The Use of Audio-Visual Media to Improve Early Childhood Language Development - Primastuty, Isnania; Asmawulan, Tri (Universitas Muhammadiyah Surakarta, 2023)
Early childhood, typically the developmental stage from birth to six years old, is often regarded as the “golden age” of human development. Children are expected to achieve significant developmental milestones across various domains during this formative period. Language development holds particular significance among these domains, as it empowers young children to effectively communicate their thoughts, feelings, and desires to parents, educators, and peers alike. Audio-visual media emerges as a potent tool in fostering language development from early childhood onward. This study aims to explore the impact of audio-visual media on young children’s language development, with a specific focus on KB Ar Rosyid Kartasura Sukoharjo. The research subjects comprise groups of 3 to 4-year-old children enrolled in the An Nahl class, totaling 20 participants, including 9 boys and 11 girls. This study uses a qualitative research approach to rely on human speech or writing and observable behavior as primary data sources. Data collection techniques encompass interviews, observations, and note-taking. The research findings from KB Ar Rosyid Kartasura Sukoharjo indicate that audio-visual media contributes positively to language development in young children.